Mortality Assessment of Pediatric Septic Patients Through Pediatric Sofa+Anion Gap and Pelod-2 Scores - Johaan Pawe Siampa; Arie Utariani; Elizeus Hanindito (Folia Medica Indonesiana, 2022)
Highlight: